An Evaluation Model Based on the Fuzzy AHP for Teleoperation Performance. Issue 1 (3rd April 2019) - Wang, Chao; Niu, Jianwei; Zhang, Yijing; Pan, Dan
ABSTRACT: Objective : This study is to construct a model composed of multiple indices to measure astronaut teleoperation performance. Background : Teleoperation is a key operation during spaceflight. Comprehensive scientific evaluation techniques for teleoperation performance are important for astronaut selection and training. Method : Four categories of indices, i.e., completion performance, safety performance, subjective cognitive performance and physiological parameters, were adopted in this model. The fuzzy analytic hierarchy process (AHP) was used to compute the weight coefficients of the indices to construct the linear performance model. Sixty-four male subjects were recruited to complete three teleoperation tasks, including point aiming, line alignment, and obstacle avoidance, in simulated environments. Their performance was rated by the researchers after the tasks. Results : The safety performance index had the highest weight coefficient (0.5274) of the first level indices, and the weight coefficient of the collisions index (0.8227) was the highest of the second level indices for safety performance. The linear performance model was constructed to calculate comprehensive performance values. Conclusion : Safety considerations are the most important factors for astronauts to consider in teleoperation. The collision of the robotic arm is the most vital safety index. The comprehensive value derived from the model was significantly related to overall performance. The validity of our model was verified, and it is anticipated that the model will be used to evaluate the performance of remote robotic arm operations.